METHODOLOGICAL APPROACH TO DEVELOPING ALGORITHMIC THINKING USING EDUCATIONAL ROBOTS IN CLASSROOM TEACHING - Stoković, Gordana (Metodička teorija i praksa, 2025)
Algorithmic thinking is a problem-solving approach and one of the core skills pupils develop interactively during primary education. One approach to developing algorithmic thinking is working with physical digital devices such as educational robots. The aim of this paper is to present the methodological approaches in developing algorithmic thinking using educational robots, as well as alternative approaches in case of lack of technology. The code writing is shown through 4 different methodological approaches and the transformation from the square grid into a linear algorithm. When writing the algorithm, mistakes (bugs) are inevitable, so special attention in the methodological approach is paid to recognizing and correcting mistakes (debugging), as an important skill that should be developed in the first cycle of primary education. In the absence of physical digital devices, algorithmic thinking can be developed using virtual robots-emulators, available in the web environment, or in the form of mobile applications.